Psychosocial interventions for psoriasis: a Bayesian network meta-analysis - Lingling Lu; Yujuan Xu; Meiling Shi; Aimin Liu (Journal of Dermatological Treatment)
Background Psoriasis impacts patients’ mental and physical health, prompting interest in psychosocial interventions.Aim To compare and rank different psychosocial interventions for psoriasis and their effects on well-being and mental health.Methods A systematic search was conducted using Cochrane Library, EMBASE, Medline, and PsycINFO (via the OVID) from their inception to 6 February 2024. Trials investing in psychosocial therapy in psoriasis patients were included using A random-effects network meta-analysis (NMW) within a Bayesian framework focusing on dermatology life quality index (DLQI), depression, and anxiety, along with adherence to treatment. The risk of bias was assessed by the Cochrane Handbook.Results Thirteen studies with 6 treatments and 1233 patients were included. The quality of the included studies was low. For DLQI, 9 studies were eligible, mindfulness + treatment as usual (TAU) was better than TAU (MD = −7.21, 95%CI [−14.89, 0.54]). Cognitive behavioral therapy (CBT) + TAU were more effective in improving HADS-anxiety (MD = −2.17, 95%CI [−3.86, −0.49]) and HADS-depression (MD = −1.58, 95%CI [−3.65, 0.68]). Regarding adherence, CBT + TAU (MD = 0.84, 95%CI [−0.62, 2.27]) ranked first, followed by motivational interviewing + TAU.Conclusion We confirmed the effectiveness of psychosocial interventions on patients’ well-being and mental health and recommended several interventions for clinical practice. However, the results should be cautiously interpreted, due to lacking high-quality and more replication studies.